Repeated supra-maximal sprint cycling induces endothelial stress in healthy young males - Kirk, R. J.; Peart, D. J.; Madden, L. A.; Vince, R. V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Endothelial microparticles (EMP), analysed with specific antibodies by flow cytometry provide information on the state of the endothelium (1). EMP are released either through cellular activation, injury, stress, or during apoptosis or necrosis (1). Importantly, EMP are found in the plasma of healthy subjects, being constantly shed into the circulation, as well as in various pathological conditions (2). Few studies have investigated the exercise-induced stress response on EMP release. The aim of this study was to quantify changes in biomarkers of vascular endothelium as a result of high intensity sprint cycling exercise in young healthy subjects. Methods: Seven active males volunteered for the study (22 ± 3 years, 1.82 ± 0.06 m, 81.3 ± 8.4 kg, Peak Power Output (PPO) 300 ± 22 W) and performed high intensity cycling on 3 separate visits. A PPO test and familiarisation was completed in visit 1, while sessions 2 and 3 were randomised exercise trials performed under placebo (sodium chloride (PLAC); capsules containing 0.045g.kg.BW-1 NaCl) or experimental (sodium bicarbonate (BICARB); capsules containing 0.03g.kg.BW-1 NaHCO3) conditions. Subjects completed 10 sets of 15-sec cycle sprints at 120% PPO, each separated by 45-sec of active recovery. Endothelial function was assessed by EMP using CD-105+MP and vascular cell adhesion molecule (VCAM-1+MP) as biological markers at rest (T0) and immediately (TEND), 90-min (T90) and 180-min (T180) post-exercise. Results: A significant increase in both markers was evident for each cycling condition from TEND to T90 (p<0.05) with no significant differences between conditions. There was a trend for EMP to return to basal levels at 180-min, with significance in CD-105+MP BICARB group, and VCAM-1+MP PLAC group (p<0.05). Data was combined regardless of condition, displaying a significant time effect for markers (p<0.001). Discussion: Repeated supra-maximal exercise was capable of increasing the concentration of EMP when compared with those levels at rest. Additionally, the levels of EMP had returned to resting values after 180-min of recovery. The significant increase in CD- 105+MP and VCAM-1+MP may be caused by increased oxidative and endothelial shear stress (3). However, the endothelium activation appears to resolve rapidly in recovery. An additional finding was no attenuation in the EMP response following NaHCO3 ingestion, suggesting EMP release is not particularly sensitive to any alterations in blood pH.